Matriks Evaluasi Risiko Penerapan IS/IT Menggunakan Standar ISO 31000:2018 (Studi Kasus: PT XYZ) - Celesta, Ivana; Ismiati, Maria Bellaniar (Yayasan Petra Harapan Bangsa, 2022)
PT XYZ is one of the largest trading companies in Palembang city. PT XYZ utilizes IS/IT to support its business processes. PT XYZ uses computers, LANs, servers, supported applications, and applications made by the IT team. IS/IT implementation at PT XYZ was not always smooth. PT XYZ had experienced problems, such as Wi-Fi problems, applications problems, not updated applications, and other human errors. PT XYZ has concerns that those problems will risk burdening the business processes in the company. The purpose of this research is to analyzee the risk of implementing IS/IT using the ISO 31000:2018 standard. All steps in IS/IT implementation risk management with ISO 31000:2018 standards have been implemented well at PT XYZ. From the results of this study, there are 21 possible risks with the risk management option plan chosen by the company, 10% risk is acceptable, 57% risk can be mitigated, 29% risk must be avoided, and 5% risk will be shared for handling the risk. Handling this risk is expected to assist the company in dealing with IS/IT implementation risks that can occur at any time.